A Geometrically Well-Defined and Systematically Tunable Experimental Model to Transition from Planar to Mesoporous Perovskite Solar Cells - Döhler, Dirk; Büttner, Pascal; Scheler, Florian; Thiel, Dominik; Puscher, Bianka; Bochmann, Sebastian; Mitrovic, Julian; Boix, Pablo P.; Guldi, Dirk Michael; Minguez-Bacho, Ignacio; Bachmann, Julien (ACS Applied Energy Materials, 2022)
A series of perovskite solar cells with systematically varying surface area of the interface between n-type electron conducting layer (TiO2) and perovskite are prepared by using an ordered array of straight, cylindrical nanopores generated by anodizing an aluminum layer evaporated onto a transparent conducting electrode. A series of samples with pore length varied from 100 to 500 nm are compared to each other and complemented by a classical planar cell and a mesoporous counterpart. All samples are characterized in terms of morphology, chemistry, optical properties, and performance. All samples absorb light to the same degree, and the increased interface area does not generate enhanced recombination. However, the short circuit current density increases monotonically with the specific surface area, indicating improved charge extraction efficiency. The importance of the slow interfacial rearrangement of ions associated with planar perovskite cells is shown to decrease in a systematic manner as the interfacial surface area increases. The results demonstrate that planar and mesoporous cells obey to the same physical principles and differ from each other quantitatively, not qualitatively. Additionally, the study shows that a significantly lower TiO2 surface area compared to mesoporous TiO(2 )is needed for an equal charge extraction.
CRIS-Team WoS Importer:2022-10-14